Acupuncture for the treatment of overactive bladder: A systematic review and meta-analysis - Lee, Jung-Ju; Heo, Jeong-Weon; Choi, Tae-Young; Jun, Ji Hee; Lee, Myeong Soo; Kim, Jong-In (Frontiers in Neurology, 2023)
Background: Acupuncture (AT) successfully regulates overactive bladder (OAB) symptoms. However, previous systematic reviews and meta-analyses have not provided sufficient evidence. This review presents the current evidence of the efficacy of AT in the management of OAB symptoms. Methods and analyses: Twelve databases were searched from their inception: the PubMed, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), and AMED databases; five Korean medical databases; and three Chinese medical databases. Study selection, data extraction, and assessment were independently performed by two researchers. The risk of bias was assessed using the Cochrane risk of bias assessment tool. RevMan 5.4.1 software was used for data aggregation, and the Grades of Recommendation, Assessment, Development and Evaluation (GRADE) assessment was used to evaluate the quality of the study outcomes. Results: Thirty studies were included in this review. Compared with the sham AT group, the AT group exhibited significant effects in reducing overactive bladder symptom scores (OABSS) (mean difference (MD), -1.13, 95% confidence interval (CI) -2.01 to -0.26, p=0.01 I2=67%) and urinary frequency (standard mean difference (SMD), - 0.35, 95% CI -0.62 to -0.08, I2=0%). The AT group showed an equivalent effect as drug therapy in reducing OABSS (MD, -0.39, 95% CI - 1.92 to 1.13, p=0.61, I2=94%) and urinary frequency (MD, 0.74, 95% CI -0.00 to 1.48 p=0.05, I2=71%) with fewer adverse events (risk ratio (RR), 0.38, 95% CI 0.16 to 0.92, p=0.03, I2=58%). The AT plus drug therapy group had a more favorable effect than drug therapy alone for reducing OABSS (MD, -2.28, 95% CI -3.25 to -1.31, p<0.00001, I2=84%) and urinary frequency (MD, -2.34, 95% CI -3.29 to -1.38, p<0.00001, I2=88%). The GRADE assessment demonstrated that the level of evidence was mostly low or very low given the high risk of bias and small sample sizes. Conclusions: AT had more favorable effects than sham AT in reducing OAB symptoms. AT improved OAB symptoms as effectively as conventional drug therapy, and the combination of AT and drug therapy had more favorable effects than drug therapy alone. However, more rigorous studies are needed to enhance the level of evidence.